Quantifying spatial heterogeneity of vulnerability to short-term PM2.5 exposure with data fusion framework. (15th September 2021) - Kuo, Cheng-Pin; Fu, Joshua S.; Wu, Pei-Chih; Cheng, Tain-Junn; Chiu, Tsu-Yun; Huang, Chun-Sheng; Wu, Chang-Fu; Lai, Li-Wei; Lai, Hsin-Chih; Liang, Ciao-Kai
Abstract: The current estimations of the burden of disease (BD) of PM2.5 exposure is still potentially biased by two factors: ignorance of heterogeneous vulnerabilities at diverse urbanization levels and reliance on the risk estimates from existing literature, usually from different locations. Our objectives are (1) to build up a data fusion framework to estimate the burden of PM2.5 exposure while evaluating local risks simultaneously and (2) to quantify their spatial heterogeneity, relationship to land-use characteristics, and derived uncertainties when calculating the disease burdens. The feature of this study is applying six local databases to extract PM2.5 exposure risk and the BD information, including the risks of death, cardiovascular disease (CVD), and respiratory disease (RD), and their spatial heterogeneities through our data fusion framework. We applied the developed framework to Tainan City in Taiwan as a use case estimated the risks by using 2006–2016 emergency department visit data, air quality monitoring data, and land-use characteristics and further estimated the BD caused by daily PM2.5 exposure in 2013. Our results found that the risks of CVD and RD in highly urbanized areas and death in rural areas could reach 1.20–1.57 times higher than average. Furthermore, we performed a sensitivity analysis to assess the uncertainty of BD estimations from utilizing different data sources, and the results showed that the uncertainty of the BD estimations could be contributed by different PM2.5 exposure data (20–32%) and risk values (0–86%), especially for highly urbanized areas. In conclusion, our approach for estimating BD based on local databases has the potential to be generalized to the developing and overpopulated countries and to support local air quality and health management plans. Graphical abstract: Image 1 Highlights: The developed framework can estimate local PM2.5 exposure risk and disease burden. Risks for urban and rural areas were 1.20–1.57 times higher than average. Spatial heterogeneity of risk can bias nationwide burden estimations and GBD.